2013
DOI: 10.4236/health.2013.51008
|View full text |Cite
|
Sign up to set email alerts
|

Health care services in India: A few questions on equity

Abstract: This paper analyzes equity in health care utilizetion and out-of-pocket expenditure on health care in India using two rounds (52th round 1995-1996 and 60th round 2004-2005) of National Sample Survey data and data from a household survey carried out in 2007. The findings indicate that the average hospitalization rate has increased and the correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The finding that spending was highly regressive is in line with findings from national studies describing the regressive nature of total health care financing/payments in these two countries [ 30 , 31 ]. India and Kenya have different health systems structures in that India has a decentralised public health system, while Kenya’s system is highly centralized [ 30 , 31 ]. However, both settings are pluralistic, with a significant proportion of services offered either by private providers or by public providers charging users fees at the point of use.…”
Section: Discussionsupporting
confidence: 86%
“…The finding that spending was highly regressive is in line with findings from national studies describing the regressive nature of total health care financing/payments in these two countries [ 30 , 31 ]. India and Kenya have different health systems structures in that India has a decentralised public health system, while Kenya’s system is highly centralized [ 30 , 31 ]. However, both settings are pluralistic, with a significant proportion of services offered either by private providers or by public providers charging users fees at the point of use.…”
Section: Discussionsupporting
confidence: 86%
“…We provide some plausible explanations. Public health centers continues to be the mainstay of health services for the poor while rich people preferring to use private health services [63, 64]. This is due to the higher ability to pay for health services among the non-poor, health system of the state and access to health insurance / reimbursement mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The regressive system of OOPP for hospitalisation in 2014 is an important finding from a policy perspective. A previous study in India showed that the OOPP for hospitalisation was regressive in 2004 ( Mondal, 2013 ). OOPP in most countries is an especially regressive means of raising healthcare revenues indicating the inability and weakness of the healthcare system in financing and protecting its poor population from negative health shocks ( Pannarunothai and Mills, 1997 , Cisse et al, 2007 , Akazili et al, 2011 , Baji et al, 2012 , Munge and Briggs, 2014 , Bock et al, 2014 , Rezapour et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%